Melatonin suppresses TPA‐induced metastasis by downregulating matrix metalloproteinase‐9 expression through JNK/SP‐1 signaling in nasopharyngeal carcinoma. Issue 4 (24th September 2016) - Ho, Hsin‐Yu; Lin, Chiao‐Wen; Chien, Ming‐Hsien; Reiter, Russel J.; Su, Shih‐Chi; Hsieh, Yi‐Hsien; Yang, Shun‐Fa
Abstract: Nasopharyngeal carcinoma (NPC), a disease common in the South‐East Asian population, has high lymph node metastatic ability. Melatonin, an endogenously produced substance present in animals, plants, fungi, and bacteria, has oncostatic activity via several mechanisms. The molecular mechanisms involved in melatonin‐mediated tumor inhibitory potential are not completely defined. Here, we show that melatonin treatment inhibits TPA‐induced cell motility by regulating the matrix metalloproteinase‐9 (MMP‐9) expression in NPC. We also identified the signaling cascade through which melatonin inhibits MMP‐9 expression; this involves melatonin regulating the binding activity of the transcription factor specificity protein‐1 (SP‐1)‐DNA. Our mechanistic analysis further reveals that the c‐Jun N‐terminal kinase/mitogen‐activated protein kinase pathway is involved in the melatonin‐mediated tumor suppressor activity. Furthermore, the findings indicate a functional link between melatonin‐mediated MMP‐9 regulation and tumor suppressing ability and provide new insights into the role of melatonin‐induced molecular and epigenetic regulation of tumor growth. Thus, we conclude that melatonin suppresses the motility of NPC by regulating TPA‐induced MMP‐9 gene expression via inhibiting SP‐1‐DNA binding ability. The results provide a functional link between melatonin‐mediated SP‐1 regulation and the antimetastatic actions of melatonin on nasopharyngeal carcinoma.